How to use CRISPR/Cas9 in plants: from target site selection to DNA repair - Přibylová, Adéla; Fischer, Lukáš (Journal of experimental botany, 2024)
A tool for precise, target-specific, efficient, and affordable genome editing is a dream for many researchers, from those who conduct basic research to those who use it for applied research. Since 2012, we have tool that almost fulfils such requirements; it is based on clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas) systems. However, even CRISPR/Cas has limitations and obstacles that might surprise its users. In this review, we focus on the most frequently used variant, CRISPR/Cas9 from Streptococcus pyogenes, and highlight key factors affecting its mutagenesis outcomes: (i) factors affecting the CRISPR/Cas9 activity, such as the effect of the target sequence, chromatin state, or Cas9 variant, and how long it remains in place after cleavage; and (ii) factors affecting the follow-up DNA repair mechanisms including mostly the cell type and cell cycle phase, but also, for example, the type of DNA ends produced by Cas9 cleavage (blunt/staggered). Moreover, we note some differences between using CRISPR/Cas9 in plants, yeasts, and animals, as knowledge from individual kingdoms is not fully transferable. Awareness of these factors can increase the likelihood of achieving the expected results of plant genome editing, for which we provide detailed guidelines.
Keywords: Plants; CRISPR-Cas Systems; DNA Repair; Cell cycle; Gene Editing; mutagenesis; staggered ends; CRISPR-Cas systémy; post-cleavage trimming; cleavage; plants; editace genu; DNA repair; rostliny; CRISPR/Cas; oprava DNA; editing